Study on the Error Transfer of Articulated Arm Coordinate Measuring Machines - Guanbin Gao; Wen Wang; Jianjun Zhou (Institute of Advanced Engineering and Science, 2013)
The articulated arm coordinate measuring machine (AACMM) is a new type coordinate measuring machine (CMM) base on the linkage structure. The kinematic model of a 6-DOF AACMM with DH method was established, and from the kinematic model the coordinate systems and joint structural parameters of the AACMM are obtained. The Jacobian matrix was deduced by differential transformation from the kinematic model of the AACMM, and according to the Jacobian matrix, the error transfer coefficients of the joint structural parameters were calculated. Then with the calculation results the influence of the joint structural parameters on the measuring accuracy of the AACMM was analyzed, which provides a theoretical basis for calibration, tolerance distribution of the joint parts and components' selection of the AACMM. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1987